2022
DOI: 10.3390/rs14092081
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing Survey of Altiplano-Puna Volcanic Complex Rocks and Minerals for Planetary Analog Use

Abstract: The Altiplano-Puna Volcanic Complex (APVC) of the Central Andes is an arid region with extensive volcanism, possessing various geological features comparable to those of other solar system objects. The unique features of the APVC, e.g., hydrothermal fields and evaporite salars, have been used as planetary analogs before, but the complexity of the APVC presents a wealth of opportunities for more analog studies that have not been exploited previously. Motivated by the potential of using the APVC as an analog of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…Similar results were obtained when mixing large plagioclase crystals (>∼840 μm) with as much as 50 vol % of ferro‐magnesian minerals (Rogers & Nekvasil, 2015). More recently, analog studies of the Atacama Desert of northern Chile reported plagioclase‐like signatures in the VNIR remote sensing data set of dacitic domes and ignimbrite sheets (Ito et al., 2022). We therefore conclude that materials with relatively large plagioclase crystals, such as porphyritic basalts (or more evolved effusive rocks) and/or with few mafic minerals, such as ignimbrite sheets, could be consistent with some of the weaker feldspathic detections identified from VNIR data, such as those in VM.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained when mixing large plagioclase crystals (>∼840 μm) with as much as 50 vol % of ferro‐magnesian minerals (Rogers & Nekvasil, 2015). More recently, analog studies of the Atacama Desert of northern Chile reported plagioclase‐like signatures in the VNIR remote sensing data set of dacitic domes and ignimbrite sheets (Ito et al., 2022). We therefore conclude that materials with relatively large plagioclase crystals, such as porphyritic basalts (or more evolved effusive rocks) and/or with few mafic minerals, such as ignimbrite sheets, could be consistent with some of the weaker feldspathic detections identified from VNIR data, such as those in VM.…”
Section: Discussionmentioning
confidence: 99%
“…Sandstone is a kind of consolidated sandy rock that is silicon-rich and has high hardness and high melting point [1]. Tis mineral usually includes siliceous, carbonate, iron, gypsum, phosphate, and chlorite, of which the content of quartz and siliceous cutting exceeds 95% with greater transparency.…”
Section: Introductionmentioning
confidence: 99%